Tongue development in stillborns autopsied at different gestational ages - Laura S. Aguiar; Guilherme R. Juliano; Luciano A.M. Silveira; Mariana S. Oliveira; Bianca G.S. Torquato; Gabriela R. Juliano; Márcia F. Araújo; Sanivia Aparecida L. Pereira; Vicente de Paula A. Teixeira; Mara Lúcia F. Ferraz (Elsevier, 2018)
Objectives: This study aimed to analyze, through the morphometric method, the perimeter and length of the tongue, the collagen fibers, and the perimeter of blood vessels at different gestational ages and fetal weights. Material and methods: Tongues (n = 55) of stillborns autopsied at 23-40 weeks of gestational age were macroscopically analyzed, and their length and perimeter were measured. Fifty-five tongue fragments were collected through a longitudinal section in the region that accompanies the median lingual sulcus and histologically processed. Slides were stained with picrosirius and immunolabeled with CD31 antibody. Quantification was performed on collagen fibers under polarized light, and on the perimeter of vessels with the CD31. Results: A positive and significant correlation of gestational age with tongue perimeter and length was found. There was a positive and significant correlation between collagen fibers and gestational age, as well as between gestational age and the perimeter of blood vessels. Between collagen fibers and fetal weight, a positive and significant increase was observed. Regarding the correlation between the perimeter of blood vessels and the fetal weight, an increase was observed. Conclusion: As gestational age advances, there is an increase in tongue perimeter and length, in the percentage of collagen fibers, and in vascular perimeter, demonstrating that tongue formation is directly related to tongue growth and development. Resumo: Objetivos: Analisar, por meio do método morfométrico, o perímetro e o comprimento da língua, as fibras de colágeno, o perímetro dos vasos sanguíneos, em idades gestacionais e de acordo com o peso fetal. Materiais e métodos: Línguas (n = 55) de natimortos autopsiados com 23-40 semanas de idade gestacional foram analisadas macroscopicamente, medidas em comprimento e perímetro; 55 fragmentos das línguas foram coletados por meio de uma secção longitudinal na região que acompanha o sulco lingual médio e processados histologicamente. As lâminas foram coloridas com picrosirius e imunomarcadas com o anticorpo CD31. A quantificação foi feita em fibras de colágeno examinadas com microscópio de luz polarizada e o perímetro dos vasos com o CD31. Resultados: Foi encontrada uma correlação positiva e significativa da idade gestacional com o perímetro e o comprimento da língua. Houve uma correlação positiva e significativa entre as fibras de colágeno e a idade gestacional; bem como entre a idade gestacional e o perímetro dos vasos sanguíneos; e houve um aumento positivo e significativo entre as fibras de colágeno e o peso fetal. No que diz respeito à correlação entre o perímetro dos vasos sanguíneos e o peso fetal, houve um aumento. Conclusão: Conforme a idade gestacional avança, há um aumento no perímetro e no comprimento da língua, um aumento no percentual de fibras de colágeno e um aumento no perímetro vascular, demonstra que a formação da língua está diretamente relacionada ao crescimento e ao desenvolvimento da língua. Keywords: Gestational age, Stillborn, Autopsy, Palavras-chave: Idade gestacional, Natimortos, Autópsia